Ekonomin i syrning av spannmål till mjölkkor - Heiding, Daniel (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
In this dissertation I have tried to figure out if it possible to make any money on acid grain to feed cows through a case study. The method is a case study combined with a documentary research. At present the farm sell all grain in connection with harvest and buy it back continuously in the neighbourhood, I have compared that with an alternative where I invest in a construction for to store acid grain on the current farm. I have delimit me to only have a look on acid grain because I think that is one of the cheapest way too store grain in smaller aplenty. Before beginning with acid grain is it important to be versed in how everything works and the risk to keep on with acid grain. One disadvantage is that the acid grain is not possible to store more than 12 months with out acid it once again. It is also easy to get mould in the pasture if it is not acid enough. The advantage with to acid grain is that it gives a more tasty pasture, its not dusty and gives a possibility to store one`s own grain on the farm without a high investment. I calculated the alternatives to invest in this system compared to sale the grain in connection with the harvest. The study shows that is profitable to acid your own grain and keep it home on the farm but not as profitable as I thought before I begin this work.